Morphological aspects of fruits, seeds, and seedlings, and anatomy of seedlings of apuleia molaris spruce ex benth - REIS, Alisson Rodrigo Souza (Associação Brasileira de Tecnologia de Sementes, 2017)
Apuleia molaris spruce ex benth, commonly known in Brazil as "amarelão," is a fast-growing forest plant with a potential for use in reforestation; however, there is little information about the physiology and morphology of its fruits, seeds, and seedlings. Thus, the objective of this work was to describe the morphology of the fruits, seeds, and seedlings, in addition to the anatomic patterns of seedlings, as a contribution to the technical-scientific knowledge and production of amazonian species for reforestation in the state of Pará. For this purpose, the morphological descriptions followed the parameters from specialized literature and the common techniques used in plant anatomy. The species presents leguminous fruit; seeds with pleurogram, average dimensions of 51.21, 21.33, and 2.09 mm length, width, and thickness, respectively; and seedlings with eophyll and pinnate metaphylls, cordiform, phanerocotylar germination, epigaeous, and foliaceous. Eophylls and metaphylls present uniseriate epidermis, collateral and dorsiventral vascular bundle. The morphological characteristics may help in field identification and in the identification of young plants, aiding the production of seedlings of this species. Furthermore, anatomically, the hypocotyl has no striking differences from the root.